2022
DOI: 10.3389/froh.2022.981343
|View full text |Cite
|
Sign up to set email alerts
|

Aggregatibacter actinomycetemcomitans and Filifactor alocis: Two exotoxin-producing oral pathogens

Abstract: Periodontitis is a dysbiotic disease caused by the interplay between the microbial ecosystem present in the disease with the dysregulated host immune response. The disease-associated microbial community is formed by the presence of established oral pathogens like Aggregatibacter actinomycetemcomitans as well as by newly dominant species like Filifactor alocis. These two oral pathogens prevail and grow within the periodontal pocket which highlights their ability to evade the host immune response. This review fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The latter contributes to the degradation of H 2 O 2 produced by neutrophils and streptococci, protecting A.a from oxidative damage [ 19 ]. The release of cytolethal distension toxin in this environment inhibits phagocytosis, and the release of leukotoxin by A.a promotes neutrophil degranulation or death, which leads to the promotion of bone resorption [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter contributes to the degradation of H 2 O 2 produced by neutrophils and streptococci, protecting A.a from oxidative damage [ 19 ]. The release of cytolethal distension toxin in this environment inhibits phagocytosis, and the release of leukotoxin by A.a promotes neutrophil degranulation or death, which leads to the promotion of bone resorption [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The role of Granulicatella in the periodontal biofilm is less clear, while G. adiacens has shown the ability to co-aggregate with F. nucleatum [31]. Along with the classical periodontal pathogens described by Socransky et al [32][33][34], the list of taxa associated with periodontitis in the present study includes some bacteria recently associated with periodontitis such as Fretibacterium [35], Dialister pneumosintes [36] and Filifactor alocis [37][38][39]. These associations are confirmatory although novel in relation to this specific population of patients with minimal dental care, and all are affected by Mets.…”
Section: Discussionmentioning
confidence: 58%
“…For example, in addition to the primary members of the red and orange complexes, there are other bacteria that have been suggested to be involved in PDs. These include: Filifactor alocis, Fretibacterium fastidiosum, Eikenella corrodens, Capnocytophaga spp ., and Aggregatibacter actinomycetemcomitans , the last three genera already associated with the yellow and green complexes, respectively, whose members are more commonly associated with periodontal health contexts ( Gholizadeh et al, 2017 ; Kang et al, 2021 ; Ozuna et al, 2022 ; Pandian et al, 2023 ). Kang et al (2021) concluded that beyond the red complex T. forsythia and the orange complex C. rectus , F. fastidiosum is also a key driver during microbiota alteration in the progression of periodontitis.…”
Section: Exploring Bacterial Complexesmentioning
confidence: 99%